Enhancing functional antibody responses against HIV envelope V1V2 through vaccine formulations - Yengo, Clauvis Kunkeng; Liu, Xiaomei; Laghlali, Gabriel; Park, Seok-Chan; Klingler, Jéromine; Luo, Christina C.; Jiang, Xunqing; Kong, Xiang-Peng; Rao, Priyanka G.; Upadhyay, Chitra; Wiest, Matthew J.; Muramatsu, Hiromi; et al. (Frontiers in Immunology, 2025)
BackgroundDespite decades of research, the development of an effective HIV vaccine remains a significant challenge. Recent findings from three large vaccine efficacy trials have identified antibodies against the V1V2 domain of the HIV envelope glycoprotein as a potential correlate of reduced infection risk, offering a promising avenue for improving vaccine efficacy. Vaccine-elicited anti-V1V2 antibodies do not mediate potent virus-neutralizing activities, but they mediate Fc-dependent effector functions.MethodsThis study evaluated the capacity of V1V2-scaffold vaccines in different formulations to generate antibody responses with Fc-mediated functions. BALB/c mice were immunized with V1V2-scaffold proteins formulated with one of the following adjuvants: MF59-like squalene-based oil-in-water emulsion (Addavax), a combination of TLR7/8 and RIG-I agonists (IMDQ-PC/IVT), nanoemulsion and RIG-I agonist (NE/IVT), or empty lipid nanoparticles (eLNP). All formulations were administered intramuscularly except NE/IVT, which was given intranasally. For comparison, we also tested a V1V2-scaffold-expressing mRNA-LNP vaccine delivered intramuscularly and an Env gp140 protein with liposomal MPLA/DDA adjuvant administered subcutaneously.ResultsAmong the six vaccine formulations tested, V1V2-scaffold immunogens adjuvanted with LNP (eLNP and mRNA-LNP) elicited the most robust and cross-reactive serum IgG responses that recognized native Env on cell surfaces or virions. The eLNP and mRNA-LNP groups, along with IMDQ-PC/IVT, also elicited functional IgG2a, and correspondingly displayed Fc-mediated activities, as measured by antibody-dependent cellular phagocytosis and FcγRIV binding. Notably, IMDQ-PC/IVT elicited predominantly IgG2a with minimal IgG1, eLNP stimulated IgG1 and IgG2a with IgG1 dominance, whereas mRNA-LNP yielded more balanced IgG2a/IgG1 responses.ConclusionsData from this study provide new insights into the utility of novel formulations for V1V2-scaffold immunogens as a strategy for optimizing the induction of functional V1V2-specific antibodies to improve HIV vaccine efficacy.